Pemberdayaan Masyarakat Melalui Pembentukan Factory Sharing Produk Olahan Susu Desa Tenjolaya - Cintantya Andhita Dara Kirana; Siti Widharetno Mursalim; Refri Shafrudin; Bahril Putra Ardian; Septi Lestari (Politeknik STIA LAN Bandung, 2023)
Community empowerment is one approach in development studies with the aim of involving the community in development activities and maximizing the resources owned to achieve the welfare of the local community. One of the potential things that can be developed by a village is the agricultural and livestock sector. Tenjolaya Village is one of the villages in Bandung Regency that excels in the agricultural and livestock sector, one of the leading products of Tenjolaya Village is fresh cow's milk. There are problems that occur in Tenjolaya Village in the management of dairy products, including the lack of knowledge, capacity and facilities of residents in producing and marketing cow's milk products. One of the efforts to optimize livestock results in the form of cow's milk is to take an empowerment approach for the community. The team of lecturers and students of STIA LAN Polytechnic Bandung through the Business Incubator (Bicube) of STIA LAN Polytechnic Bandung conducted business assistance in an effort to empower the people of Tenjolaya Village through the establishment of factory sharing. The result of Tenjolaya Village community empowerment activities is the establishment of factory sharing and the development of fresh cow's milk products which were originally only cow's milk, now developed into several products, namely milk candy, nougat and milk sticks.